(untitled) (American Journal of Islam and Society, 2010)
In the post-9/11 era and with increasing tension between the Islamic and the non-Islamic worlds due to al-Qa’ida’s purported global jihad, Labeeb Bsoul’s study of the Islamic law of international treaties is certainly a timely contribution to an important topic. While this work represents a fairly comprehensive resource for researchers in this area insofar as it gathers the opinions of numerous pre-modern (and some modern) scholars of Islamic law on various issues related to war and peace between Islamic and non-Muslim states, it is, unfortunately, no more than a simple compilation of their views. Indeed, the author provides no meaningful historical framework by which one could trace doctrinal development or tie these doctrines to a wider historical or philosophical tradition of international law. Those looking for answers regarding the possibilities for mutual co-existence between Muslim and non-Muslim states on the basis of mutual equality will be severely disappointed ...